2006
DOI: 10.4067/s0716-97602006000200018
|View full text |Cite
|
Sign up to set email alerts
|

Generation and analysis of expressed sequence tags from Botrytis cinerea

Abstract: Botrytis cinerea is a filamentous plant pathogen of a wide range of plant species, and its infection may cause enormous damage both during plant growth and in the post-harvest phase. We have constructed a cDNA library from an isolate of B. cinerea and have sequenced 11,482 expressed sequence tags that were assembled into 1,003 contigs sequences and 3,032 singletons. Approximately 81% of the unigenes showed significant similarity to genes coding for proteins with known functions: more than 50% of the sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…For hybridization, Nimblegene 4-plex arrays, containing 4 ϫ 72,000 arrays per slide, were used. Three 60-mer oligonucleotides per gene were immobilized for a total number of 20,885 predicted genes of the two sequenced B. cinerea strains B05.10 and T4, with 3,189 T4-specific genes and 1,776 B05.10-specific genes (designated BC1G_XXXX) (38). Genes annotated according to strain T4 (http://urgi .versailles.inra.fr/gb2/gbrowse/BOTRYTIS_T4_pub/) are referred to as in the abbreviated form PXXXXXX, instead of BofuT4_PXXXXXX.1, throughout this article.…”
Section: Methodsmentioning
confidence: 99%
“…For hybridization, Nimblegene 4-plex arrays, containing 4 ϫ 72,000 arrays per slide, were used. Three 60-mer oligonucleotides per gene were immobilized for a total number of 20,885 predicted genes of the two sequenced B. cinerea strains B05.10 and T4, with 3,189 T4-specific genes and 1,776 B05.10-specific genes (designated BC1G_XXXX) (38). Genes annotated according to strain T4 (http://urgi .versailles.inra.fr/gb2/gbrowse/BOTRYTIS_T4_pub/) are referred to as in the abbreviated form PXXXXXX, instead of BofuT4_PXXXXXX.1, throughout this article.…”
Section: Methodsmentioning
confidence: 99%
“…The hex gene from B. cinerea was identified and isolated from a cDNA genomic library of this fungus (Silva et al 2006). The predicted protein HEX-1 from B. cinerea shares 71 and 76% identity with the HEX protein from N. crassa and M. grisea, respectively (Asiegbu et al 2004;Tenney et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…From a B. cinerea cDNA library described previously (Silva et al 2006), we identified a sequence highly homologous to the hex-1 gene from N. crassa (AF001033). Gene-specific primers were designed and used to amplify the Bchex gene from genomic DNA of B. cinerea strain A1.…”
Section: Identification and Characterization Of Bchexmentioning
confidence: 99%
See 2 more Smart Citations